Distribution of attention in a gallery segment on the National Socialists' Führer cult: diving deeper into visitors' cognitive exhibition experiences using mobile eye tracking. (2nd January 2020) - Schwan, Stephan; Gussmann, Melissa; Gerjets, Peter; Drecoll, Axel; Feiber, Albert
ABSTRACT: Mobile eye tracking recordings of 20 visitors of the gallery section 'Der Führer' of the Dokumentation Obersalzberg (Germany) were analyzed to determine the distribution of the visitors' attention on a detailed level of individual exhibition elements consisting of single objects, pictures, texts, and labels. It was found that most of these elements were only briefly scanned but with a substantial variability in gaze behavior both across participants and exhibition elements. In particular, the objects and pictures primarily attracted the visitors' attention but did not necessarily lead to elaborate inspection. In contrast, the information texts were less often noticed by the visitors, but if they were noticed, the visitors tended to spend substantial time reading them. The study demonstrates that notwithstanding methodological drawbacks such as the lack of unobtrusiveness of recording or highly time-consuming coding of raw data, mobile eye tracking allows to analyze visitors' attention in a gallery with unprecedented precision.